Intervención del terapista respiratorio en paciente masculino de 61 años de edad con neumonía nosocomial. - Yépez Briones, Kayna Yamilet (2022)
Nosocomial pneumonia is considered the second most frequent nosocomial infection, with 5 to 7 cases per 1,000 discharged patients. Due to the main morbidity and mortality, the pathogenicity of the causative organism is different from community-acquired pneumonia, hospital-acquired pneumonia, ventilator-associated pneumonia, etc., and is a subgroup of respiratory bacteria infectious diseases. As nosocomial pneumonia is considered one of the 10 most common causes of death in hospitalized patients, research on this topic is very important, hence the need to explain the influencing factors and history of infection and the risk of nosocomial pneumonia in adults. patient, and prevention is necessary Measures are to avoid many situations. The objective of carrying out this study in a clinical case was to determine the factors and antecedents that affect the infectivity of nosocomial pneumonia in a 61-year-old male patient. A correct diagnosis in patients suspected of this disease will help to avoid complications in the health of these patients since this pathology is one of the main causes of death in hospitals and worries different health professionals.